PERANCANGAN KOMIK DIGITAL KISAH SYEKH SYARIF HIDAYATULLAH UNTUK ANAK USIA 10-12 TAHUN: DESIGN OF A DIGITAL COMIC ON THE STORY OF SYEKH SYARIF HIDAYATULLAH FOR CHILDREN AGED 10–12 YEARS - Azhar Zulfa Komara; Edy Purwantoro (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
This research aims to design a digital comic e-book that tells the story of Syarif Hidayatullah as a medium for introducing Islamic history figures in Indonesia. The design is based on the problem of the lack of introduction of local Islamic history figures to the younger generation, especially children aged 10-12 years, who are already familiar with the use of digital devices. The digital comic medium was chosen for its ability to effectively combine text and images, so that complex historical material can be presented in a simpler, more attractive, and easily understandable way. This design uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) design method. The analysis phase includes data collection through interviews, observations, and literature studies to understand the behavior of the target audience and historical context. The design phase focuses on compiling the comic concept, storyline, visual style, colors, and typography that are suitable for a child audience. The result of this design is a digital comic that presents the missionary journey of Syarif Hidayatullah in Pasundan Land, especially when preaching to his grandfather Prabu Siliwangi, a King in the Padjajaran Kingdom, through an interactive and relevant narrative visual for children. It is hoped that this comic can be an effective means of instilling leadership, tolerance, and the spirit of Islamic struggle in the younger generation.